Engineering of three-dimensional near-net-shape weave structures for high technical performance in carbon fibre–reinforced plastics. (July 2019) - Schindler, Stefan; Bauder, Hans-Jürgen; Wolfrum, Jürgen; Seibold, Jürgen; Stipic, Nemanja; von Wascinski, Larissa; Tilebein, Meike; Gresser, Götz Theodor
To tap the full potential of reinforcing fibres for lightweight construction of sustainable carbon fibre–reinforced plastic components, woven three-dimensional reinforcement structures open up innovative approaches by integrating functional features. In this work, a novel three-dimensional shuttle weaving technology was taken advantage of to study carbon reinforcement structures with uninterrupted load trajectories from three points of view. Mechanical principals, economic and environmental issues were focused to provide an overall picture. Near-net-shape reinforcement fabrics with load trajectory–compliant yarn paths and interconnected layers that are interwoven in thickness direction were objects of investigation. The effects of a closed fabric selvedge, only producible by shuttle weaving, were investigated too. The here presented novel technology enables complex woven reinforcement structures that otherwise would demand several fabric layers leading to limited properties and lower performance of the carbon fibre–reinforced plastics due to missing interconnections between the layers. The studies on exemplary rods revealed a close relationship between different three-dimensional weave structures and the carbon fibre–reinforced plastic's mechanical properties. The three-dimensional structures were woven in a single-step process and subsequently infiltrated with epoxy resin in the Vacuum Assisted Process (VAP ® ) and mechanically tested. Rounding off, universal guidelines for the layout of three-dimensional fabrics for rods were derived therefrom. The economic and environmental aspects of the complete process line were compared to the conventional manufacturing procedures for carbon fibre–reinforced plastic by material flow cost accounting. Looking at sustainability, material flow cost accounting showed that lightweight three-dimensional components with integrated features can be produced cost-effectively with less environmental impact by the novel weaving technology. Its capability for high-quality serial production of three-dimensional reinforcement structures is evident, which was one major result of the work.